Tinea faciei in a child complicated by nosocomial infection with Stenotrophomonas maltophilia – a case report - Myśliwiec, Hanna; Flisiak, Iwona; Baran, Anna; Chodynicka, Bożena (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction . Tinea faciei is quite a rare infection in the developed countries. Proper diagnosis of the causative pathogen is essential for successful treatment. Objective . To present the case of an 11-year-old patient in whom wrong diagnosis and treatment led to complications and finally to face deformation. Case report . A small inflammatory skin lesion appeared on the chin and extended quickly to form a deep infiltration. Despite surgical incision, drainage and broad-spectrum antibiotics, the skin lesion progressed to an ulceration of 2 × 3 cm in diameter with necrotic crust. In direct mycological smear hyphae were observed and in the culture Stenotrophomonas maltophilia was found. Systemic treatment with terbinafine and trimethoprim-sulfamethoxazole led to almost complete healing with a scar and chin deformation as a result. Conclusions . In the differential diagnosis of skin lesions on the chin fungal infection should always be considered, confirmed or ruled out before starting the therapy.